The size of apolipoprotein (a) is an independent determinant of the reduction in lipoprotein (a) induced by PCSK9 inhibitors. Issue 9 (27th July 2021) - Blanchard, Valentin; Chemello, Kévin; Hollstein, Tim; Hong-Fong, Clément Chong; Schumann, Friederike; Grenkowitz, Thomas; Nativel, Brice; Coassin, Stefan; Croyal, Mikaël; Kassner, Ursula; Lamina, Claudia; Steinhagen-Thiessen, Elisabeth; et al.
Abstract: Aims: Lipoprotein (a) [Lp(a)] is a lipoprotein species causatively associated with atherosclerosis. Unlike statins, PCSK9 inhibitors (PCSK9i) reduce Lp(a), but this reduction is highly variable. Levels of Lp(a) are chiefly governed by the size of its signature protein, apolipoprotein (a) [apo(a)]. Whether this parameter determines some of the reduction in Lp(a) induced by PCSK9i remains unknown. We aimed to investigate if the Lp(a) lowering efficacy of PCSK9i is modulated by the size of apo(a), which is genetically determined by the variable number of KIV domains present on that protein. Methods and results: The levels of Lp(a) and the size of apo(a) were assessed in plasma samples from 268 patients before and after treatment with PCSK9i. Patients were recruited at the Outpatient Lipid Clinic of the Charité Hospital (Berlin) between 2015 and 2020. They were hypercholesterolaemic at very high cardiovascular disease risk with low-density lipoprotein (LDL)-cholesterol levels above therapeutic targets despite maximally tolerated lipid-lowering therapy. Patients received either Alirocumab (75 or 150 mg) or Evolocumab (140 mg) every 2 weeks. Apo(a), apoB100, and apoE concentrations as well as apoE major isoforms were determined by liquid chromatography high-resolution mass spectrometry. Apo(a) isoforms sizes were determined by western blot. PCSK9i sharply reduced LDL-cholesterol (−57%), apoB100 (−47%), and Lp(a) (−36%). There was a positive correlation between the size of apo(a) and the relative reduction in Lp(a) induced by PCSK9i ( r  = 0.363, P  = 0.0001). The strength of this association remained unaltered after adjustment for baseline Lp(a) levels and all other potential confounding factors. In patients with two detectable apo(a) isoforms, there was also a positive correlation between the size of apo(a) and the reduction in Lp(a), separately for the smaller ( r  = 0.350, P  = 0.0001) and larger ( r  = 0.324, P  = 0.0003) isoforms. The relative contribution of the larger isoform to the total concentration of apo(a) was reduced from 29% to 15% ( P  < 0.0001). Conclusions: The size of apo(a) is an independent determinant of the response to PCSK9i. Each additional kringle domain is associated with a 3% additional reduction in Lp(a). This explains in part the variable efficacy of PCSK9i and allows to identify patients who will benefit most from these therapies in terms of Lp(a) lowering. Graphical Abstract: